STRATEGI PENGEMBANGAN SEKTOR PARIWISATA KABUPATEN TOBA DALAM UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH - Natalia E Sihombing; Indah Juliana Hutagalung (LPPM Universitas HKBP Nommensen, 2021)
This study aims to find out how the Toba Regency Tourism Sector Development Strategy is and how much the Tourism Sector Revenue Contribution to Toba Regency's Original Revenue is. This type of research is descriptive qualitative. The informants in this study consisted of key informants, namely the Head of the Tourism and Culture Office of Toba Regency and the Secretary of the Toba Regency's Tourism and Culture Office, the main informant was the Head of the Toba Regency Tourism Product Marketing Development Section, additional informants were the community and tourism business actors around Toba Regency tourism objects. and also the Chairperson of the Lumban Bul-Bul Beach Tourism Awareness Group with a total of 6 informants. The types of data used are primary and secondary data. Data collection techniques are interviews, observation, documentation, and also recording. The data analysis method used is processing and preparing the data for analysis, reading the entire data, analyzing in more detail by coding the data, applying the coding process, showing how the descriptions and themes will be restated in a qualitative narrative/report and interpreting or interpreting the data. The results of this study indicate that the Tourism Sector Development that has been implemented by the Tourism and Culture Office of Toba Regency is still not optimal and not maximized, this can be seen from the lack of supporting facilities and infrastructure at tourist sites, inadequate and qualified accessibility and infrastructure, awareness and participation people who are still lacking in the preservation and development of various tourism assets, the function and cooperation between tourism institutions are not yet optimal. In the development of the tourism sector, there are obstacles and obstacles in its implementation, namely: community factors, factors of lack of quality human resources, limited budget funds in the tourism sector. However, tourism development carried out by the Toba Regency Tourism and Culture Office has shown that the income from the tourism sector has been able and influential on Regional Original Revenue of Toba Regency. The percentage contribution from the Tourism sector from 2017 to 2020 is quite instrumental so that regional levies from the Tourism sector have played a role in Toba Regency's Original Revenue.